Diplomasi Pertahanan Malaysia di Laut China Selatan: Konsep dan Praktek - Simorangkir, Binsar; Tampubolon, Helga Farida; Ar Rahman, Lazuardi Loqman; Reyhan, Muhammad; Azizah, RR Zahroh Hayati (Jurnal Diplomasi Pertahanan, 2021)
The concept of defense diplomacy does not have a universally recognized definition; therefore, each country tends to have its definition, which is then included in its defense white paper. The concept of diplomacy for Malaysia itself is defined as creating stable international relations with other countries. Malaysia has a defense diplomacy strategy known as quiet diplomacy. One of the problems that threaten Malaysia's maritime economy and sovereignty that continues to this day is the South China Sea conflict. This conflict occurred because of a unilateral claim made by the Chinese government with theissuance of a map that later contained a nine-dash line. In dealing with this problem,Malaysia then implemented the concept of defense diplomacy in the multilateral realm,namely through official forums, namely the ASEAN Defense Ministers' Meeting (ADMM) and the ASEAN Defense Ministers' Meeting Plus (ADMM Plus). This report was prepared using a descriptive-narrative method obtained through interviews with resource persons and a literature study. The purpose of this report is to serve as a theoretical reference for the concepts and practices of Malaysian defense diplomacy.